Children’s online learning during COVID-19 pandemic: experiences and satisfaction encountered by Indian parents (Journal of Ideas in Health, 2021)
Background: Online learning by children is pressure for children as well as parents. The Covid-19 lockdown was ended up putting much stress on parents in India. The current study aimed to assess the parental experience and satisfaction on online learning for their children during Covid -19 pandemic lockdown.Methods: A cross-sectional web-based survey was conducted among 300 parents of children who attended online learning during the COVID -19 pandemic lockdown. The data was collected using the snowball sampling technique. The survey tool consists of a sociodemographic questionnaire, self-report scales on parent's satisfaction and experiences. The collected data were analyzed using descriptive statistics, including mean, frequency, percentage, and inferential statistics such as the Chi-square test.Results: Out of 300 parents surveyed, 72% were mothers, 65.6% of children who attended online classes were from primary class, through zoom platform (52.2%) using an android mobile phone (71.1%) for a mean duration of 180±30 minutes. 80.4% of parents preferred the traditional learning method comparing to online classes for their children. More than half (52.2%) of parents reported that they were partially satisfied with children's online learning, whereas 26% were not satisfied. More than half of the parents (61.1%) experienced a great challenge and burden of online learning.Conclusion: Parents were worried that prolonged exposure to screen devices in online learning might affect child health's visual, physical, and psychological aspects.
Keywords: Parental Satisfaction, Experience, Online Class, Covid-19 Pandemic, Lockdown, India